Analisis Pemerintahan Terbuka: Sebuah Kasus dari Banggai - Syed Agung Afandi; Rizki Erdayani; Muslim Afandi (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
This research aims to analyze the bibliometrics of Banggai open government and the policy content of Banggai Regency in implementing open government. This research uses a qualitative approach with bibliometric analysis and content analysis methods. This research uses secondary data sourced from google scholar and Banggai government policy documents. The results of this research show that there are 130 studies, 786 citations, 14 h-index, and 24 g-index. This shows that this study is in demand and has high productivity. There are 1242 total link strengths, 456 occurrences, 104 items, and 12 clusters. Themes that rarely receive attention are standard data, collaboration, the private sector, inclusiveness, and data publication. These themes have the potential to be studied in the future. There is harmony between the dominant themes and Banggai government policies. The themes that dominate are Banggai one data, participatory waste management, integrated agricultural systems, and pregnant women services. Meanwhile, Banggai government policies include online services for pregnant women, participatory waste management, Banggai One Data, and the utilization of yards through an integrated agricultural system. This shows that the role of researchers is very large in implementing open government in Banggai district.